Green Chemistry Influences in Organic Synthesis : a Review - Yehezkiel Steven Kurniawan; Krisfian Tata Aneka Priyangga; Philip Anggo Krisbiantoro; Arif Cahyo Imawan (Pandawa Institute, 2021)
Environmental pollution and global warming cause serious problems in human life. Since the demand for our human daily appliances had been increased by years, the organic chemical-based industries response that demand increment by increasing their production process. Because of that, the environmental pollution becomes worse and worse. Green chemistry thus was introduced to influence the chemical industries to strive for better environmental sustainability. Over 20 years, green chemistry principles have to influence the organic chemistry field especially as many researchers have put their attention on that field of research. So far, synthesis process involving organic compounds has been considered on waste prevention, safer solvents, design for high energy efficiency, and usage of renewable feedstocks. This review comprehensively discusses in brief about the implementation of green chemistry principle and their applications in the synthesis process of organic compounds.